2015
DOI: 10.7710/2162-3309.1243
|View full text |Cite
|
Sign up to set email alerts
|

Using a Data Management Plan Review Service as a Training Ground for Librarians

Abstract: INTRODUCTION Research Data Management (RDM) offers opportunities and challenges at the interface of library support and researcher needs. Libraries are in a position of balancing the capacity to provide support at the point of need while also implementing training for subject liaison librarians grounded in the practical issues and realities facing researchers and their institutions. DESCRIPTION OF PROGRAM/SERVICE The North Carolina State University (NCSU) Libraries has deployed a Data Management Plan (DMP) Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…For stakeholders to ask librarians to use these skills, librarians must first raise awareness of these new skill sets by proactively creating opportunities that will demonstrate how these skills can create solutions for their stakeholders' problems [9,10]. Others have suggested a number of different approaches for creating these opportunities, from designing enterprise-level services to creating workshop series that offer data science training opportunities for undergraduate and graduate students [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For stakeholders to ask librarians to use these skills, librarians must first raise awareness of these new skill sets by proactively creating opportunities that will demonstrate how these skills can create solutions for their stakeholders' problems [9,10]. Others have suggested a number of different approaches for creating these opportunities, from designing enterprise-level services to creating workshop series that offer data science training opportunities for undergraduate and graduate students [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In the next-steps section of the article, they do not address use of this training in performance appraisals for their librarians. 30 Competencies and standards are another way in which the library literature addresses the evaluation of subsets of library work. Jennifer Lyn Soutter compared competency statements in published, peer-reviewed, U.S. and non-U.S. library and information science journal articles.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past five years, an increasing body of evidence has shown that librarians actively engage in supporting data management plans [1], teaching research data management [2, 3], and curating data [4]. Medical librarians specifically offer a variety of research data management services, including providing instruction, supporting research labs, developing institutional partnerships around data, creating infrastructure, and implementing data science and visualization services [5].…”
Section: Introductionmentioning
confidence: 99%